RAISING STUDENTS’ PRAGMATIC AWARENESS IN THE READING CLASSES USING E-MAILS - IKA PUSPITARINI (Fakultas Sastra Universitas Gresik, 2018)
This paper is aimed to discuss the importance of raising the students’ pragmatic awareness in reading classes using emails. As emails are in written forms, it is sometimes difficult to communicate by avoiding misunderstanding. There are three reasons why it becomes the best example for the students to analyze the Speech Acts’ elements in e-mails in their Reading class; (1) it is considered as authentic material. The students are able to learn how the language is used in daily life, (2) its language is a hybrid of speech and writing. Enhancing students’ pragmatic awareness will lead to certain benefits. It helps students to be able to use appropriate utterances in particular situations to avoid pragmatic mistakes; it makes students feel more certain to behave in target language culture; it helps them better understand the connotative messages in each situation, and make correct presuppositions and it gives them the chance to have a better understanding and appreciation toward their own culture and the culture of others.